2010
DOI: 10.1124/jpet.110.167478
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Decreases Apolipoprotein B100-Containing Lipoprotein Levels by Reducing Hepatic Very Low Density Lipoprotein Secretion through a Possible Diacylglycerol Acyltransferase 2 Inhibition in Obese Dogs

Abstract: Apolipoprotein B100 (apoB100) is an essential component of very low density lipoprotein (VLDL) and low-density lipoprotein (LDL), both independent markers of cardiovascular risk. Nicotinic acid (NA) is an efficacious drug for decreasing VLDL and LDL, but the underlying mechanisms are unclear. For this purpose, six obese insulin-resistant dogs were given 350 mg/day of NA for 1 week and then 500 mg/day for 3 weeks. Turnover of apoB100-containing lipoproteins was investigated using stable isotope-labeled tracers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Niacin was demonstrated to directly and noncompetitively inhibit the DGAT2 activity in HepG2 cell lines, with no effect on its mRNA level (Ganji et al, 2004). Moreover, recent animal and human studies also indicated that NA could inhibit hepatic DGAT2, which resulted in a decreased triglyceride synthesis and significantly improved hepatic steatosis (Hu et al, 2012; Le Bloc'h et al, 2010). Thus, these previous studies suggest that dietary NA may also improve alcoholic fatty liver via inhibiting DGAT2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Niacin was demonstrated to directly and noncompetitively inhibit the DGAT2 activity in HepG2 cell lines, with no effect on its mRNA level (Ganji et al, 2004). Moreover, recent animal and human studies also indicated that NA could inhibit hepatic DGAT2, which resulted in a decreased triglyceride synthesis and significantly improved hepatic steatosis (Hu et al, 2012; Le Bloc'h et al, 2010). Thus, these previous studies suggest that dietary NA may also improve alcoholic fatty liver via inhibiting DGAT2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The DGAT enzymes DGAT1 and DGAT2 play an important role in triglyceride biosynthesis. Niacin inhibits hepatic DGAT2 in cell lines and in animal studies 11 , 12 and this may contribute to its lipid-modifying effects so the DGAT2 rs3060 polymorphism was considered an appropriate primary candidate genotype to examine the pharmacogenetics of the lipid responses to niacin. DGAT1 is also important for triglyceride synthesis although there are conflicting data from studies in mice over-expressing liver DGAT1 on whether this influences hepatic very low-density lipoprotein production 22 , 23 and an in vitro study showed that niacin did not appear to affect hepatic DGAT1 activity.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Recent in vitro and animal studies have shown that niacin has a direct and noncompetitive inhibitory effect on hepatic DGAT2, and it has been suggested that this may be involved in the lipid-lowering effects of niacin. 11 , 12 DGAT1 and DGAT2 are both expressed in many of the same tissues among mammals, especially those that produce large amounts of triglycerides, eg, small intestine, adipose tissues, liver and mammary gland, and so on. 9 , 10 A functional single nucleotide polymorphism (SNP) in DGAT1 , 79T>C (rs7003945) was reported to affect promoter activity in cultured cells, and the C allele was associated with 25% to 50% increased DGAT1 expression compared with the T allele in adipocytes, intestinal cells, and hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The main drugs the dogs with CKD received (enalapril and amlodipine) have not been reported to impact lipoprotein profiles in people or dogs. Niacin has been shown to decrease LDL in dogs . This could have altered the profile of the single dog with CKD that was being treated with this supplement.…”
Section: Discussionmentioning
confidence: 99%